2012
DOI: 10.1103/physrevc.85.065801
|View full text |Cite
|
Sign up to set email alerts
|

Quenching factor for low-energy nuclear recoils in a plastic scintillator

Abstract: Plastic scintillators are widely used in industry, medicine, and scientific research, including nuclear and particle physics. Although one of their most common applications is in neutron detection, experimental data on their response to low-energy nuclear recoils are scarce. Here, the relative scintillation efficiency for neutroninduced nuclear recoils in a polystyrene-based plastic scintillator (UPS-923A) is presented, exploring recoil energies between 125 and 850 keV. Monte Carlo simulations, incorporating l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…kB e and kB α are the Birks factors for the fast electron and α-particle, respectively. Many studies show that Birks factor can be regarded as a constant independent of the type and energy of incident particle [14], [25], [41], [42]. Accordingly, (9) and (10) is combined as:…”
Section: Birks Factor (Kb)mentioning
confidence: 99%
“…kB e and kB α are the Birks factors for the fast electron and α-particle, respectively. Many studies show that Birks factor can be regarded as a constant independent of the type and energy of incident particle [14], [25], [41], [42]. Accordingly, (9) and (10) is combined as:…”
Section: Birks Factor (Kb)mentioning
confidence: 99%
“…kB e , kB α , and kB Li are the Birks factors for the fast electron, α-particle, and Li ion, respectively. Some investigations reported that kB can be also regarded as a parameter independent of the type and energy of the incident particle [19,24,29,45]. Especially, Tretyak [29], using the experimental data from dozens of reports to calculate the kB values for different organic and inorganic scintillators in response to various particles (protons, α-particles, and heavy ions), concluded that kB can be empirically considered independent of the type and energy of the particle if the measurements are conducted under the same condition.…”
Section: Birks Factor (Kb)mentioning
confidence: 99%
“…Values of the kB parameter used in the computation of the detection efficiency were chosen from those described in the literature and obtained experimentally (Hirschberg et al, 1992;Wang et al, 2012;Reichhart et al, 2012). Fig.…”
Section: Kb Parametermentioning
confidence: 99%